2007
DOI: 10.1182/blood-2007-03-078576
|View full text |Cite
|
Sign up to set email alerts
|

Safety and clinical activity of the combination of 5-azacytidine, valproic acid, and all-trans retinoic acid in acute myeloid leukemia and myelodysplastic syndrome

Abstract: The combination of a DNA hypomethylating agent with a histone deacetylase inhibitor has synergistic antileukemia activity and may restore sensitivity to all-trans retinoic acid (ATRA). We conducted a phase 1/2 study of the combination of 5-azacitidine (5-AZA), valproic acid (VPA), and ATRA in patients with acute myeloid leukemia or high-risk myelodysplastic syndrome. 5-AZA was administered subcutaneously at a fixed dose of 75 mg/m 2 daily for 7 days. VPA was dose-escalated and given orally daily for 7 days con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
265
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 371 publications
(285 citation statements)
references
References 32 publications
9
265
1
5
Order By: Relevance
“…Sixteen of the identified trials were excluded for various reasons (Figure 1). 5,8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Of the five publications considered relevant for the meta-analysis, two reported different outcomes on the same trial, of which only one was relevant. Thus, four trials including 952 patients and performed between the years 2002 and 2008 fulfilled the inclusion criteria (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen of the identified trials were excluded for various reasons (Figure 1). 5,8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Of the five publications considered relevant for the meta-analysis, two reported different outcomes on the same trial, of which only one was relevant. Thus, four trials including 952 patients and performed between the years 2002 and 2008 fulfilled the inclusion criteria (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Both drugs are particularly effective when administered at low doses, which are sometimes below 10% of their maximum tolerated doses (Issa and Kantarjian, 2009). These conditions are generally assumed to maximize DNA demethylation responses, and several studies have confirmed that drug-induced DNA demethylation occurs in patients (Issa et al, 2005;Mund et al, 2005;Soriano et al, 2007;Stresemann and Lyko, 2008). However, a direct link between DNA demethylation and clinical responses has not been demonstrated yet and there are currently no established DNA methylation biomarkers that accurately predict patient responses (Fandy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Studies in patients with advanced myeloid leukemia and myelodysplastic syndromes have shown that treatment with VPA, as monotherapy or in combination with retinoic acid, results in a reduction of malignant blast cells and hematologic improvement. [26][27][28] In addition, in an ex vivo model of acute leukemia, it has been demonstrated that VPA has the potential to relieve transcriptional repression resulting in cellular differentiation of leukemic blast cells. 29 While the clinical use of HDAC inhibitors for the treatment of hematologic malignancies is rapidly increasing, surprisingly little is known about the specific effects of different HDAC inhibitors and their molecular targets in normal hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%